PENGARUH KONSENTRASI Na-ALGINAT DAN UKURAN BEADS TERHADAP STABILITAS BEADS DAN AKTIVITAS SEL Agrobacterium tumefaciens LSU20 IMMOBIL DALAM BIODESULFURISASI DIBENZOTHIOFENA - Yoga Saputra, I Made; Semadi Antara, Nyoman; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 2 (2018): April, 2018)
The purpose of this study was to determine the concentration and size of Na-alginate beads that have the highest degradation activity of dibenzothiophene. Biodesulfurization (BDS) of dibenzothiophene (DBT) was performed using 3 Na-alginate concentrations and 3 different beads sizes in the oil model system. Biodesulfurization was performed with incubation for 24 hours. The previous research showed that sodium alginate (Na-alginate) was an appropriate immobilizing agent compared to other immobilized materials. Na-alginate 4% show the activity of the degradation of the most good that is 66.33% (bead size 2 mm), 62.99% (bead size 3 mm), 59.93% (bead size 4 mm), for concentration of 3% Na-alginate showed 65.58% (bead size 2 mm), 61.68% (bead size 3 mm) and 60.43% (bead size 4 mm), while concentration 5% showed the most low that is 64.86% (bead size 2 mm), 61.01% (bead size 3 mm), and 58.89% (bead size 4 mm). The stability test showed Na-alginate 4% have the stability and durability of the bead stronger, the test showed Na-alginate can be used up to five repeat and still have degradation activity. Key words: Biodesulfurization, Dibenzothiophene, Immobilized cells, Na-alginate.